Answer:
The red line is g(x)
Step-by-step explanation:
* To solve this problem you must to know some fact about
transformation
- If the function f(x) translated horizontally to the left
by h units, then the new function g(x) = f(x + h)
- If the function f(x) translated vertically up
by k units, then the new function g(x) = f(x) + k
- If the function f(x) translated vertically down
by k units, then the new function g(x) = f(x) – k
- A vertical stretching is the stretching of the graph away from
the x-axis
• if k > 1, the graph of y = k•f (x) is the graph of f (x) vertically
stretched by multiplying each of its y-coordinates by k.
- A vertical compression is the squeezing of the graph toward
the x-axis.
• if 0 < k < 1 (a fraction), the graph is f (x) vertically compressed
by multiplying each of its y-coordinates by k.
• if k should be negative, the vertical stretch or compress is
followed by a reflection across the x-axis.
* Now lets solve the problem
- g(x) = -1/2f(x + 2)
# x + 2 ⇒ means the graph moved 2 units to the left
# -1/2 ⇒ means the graph has vertical compressed followed
by a reflection across the x-axis, then multiply
each y-coordinate by -1/2
- The graph of f(x) intersects x-axis at point (3 , 0)
∴ The point will be (1 , 0) on g(x)
- The graph of f(x) intersects y-axis at point (0 , -6)
∴ The point will be (-2 , 3) on g(x)
* Look to the graph
# The red line is g(x)
# The blue line is f(x)
- To check your answer
# The equation of f(x) is f(x) = 2x - 6
∵ g(x) = -1/2f(x + 2)
∴ g(x) = -1/2[2(x + 2) - 6] = -1/2[2x + 4 - 6] = -1/2[2x - 2] = -x + 1
* g(x) intersect x-axis at point (1 , 0) and y-axis at point (0 , 1)